Core-shell cobalt particles Co@CoO loaded on nitrogen-doped graphene for photocatalytic water-splitting. (13th January 2020) - Qiao, Shanshan; Guo, Jia; Wang, Di; Zhang, Liugen; Hassan, Afaq; Chen, Tingxiang; Feng, Chao; Zhang, Yi; Wang, Jide
Abstract: It is of great significance to explore a bifunctional catalyst that can produce both hydrogen and oxygen to accelerate the development of water-splitting technology. In this work, Co@CoO/NG was obtained via calcinating ZIF-67 and in-situ preparation process, which exhibited excellent performance (water oxidation AQE 10.22% at λ = 450 nm and oxygen production rate 543198 μmol g −1 h −1 and hydrogen production rate 330 μmol −1 g −1 h −1 ). A comprehensive analysis of SEM, XRD, TEM, UV–vis, EIS, and PL showed that Co@CoO/NG-7 prepared has a perfect skeleton and more crystal defects, which can provide more reactive sites. The core-shell structure Co@CoO has a synergistic effect with graphene, which is beneficial to the light absorption, separation of photo-generated charges. Meanwhile, cyclic experiments of water oxidation and water reduction showed that the catalyst exhibited high stability during the reaction process. This study has provided a universal strategy to design efficient bifunctional catalyst for water-splitting. Graphical abstract: Image 1 Highlights: Co@CoO/NG was synthesized by pyrolysis of ZIF-67 and in situ preparation. Co@CoO/NG has both water reduction/oxidation catalytic activities. The synergy of Co@CoO and carbon reduce the recombination of electrons and holes. Co@CoO/NG exhibits excellent photocatalytic activity and stability.